Echocardiographic Assessment of Cardiac Structural and Functional Abnormalities in Patients With End-Stage Renal Disease Receiving Chronic Hemodialysis - Matsuo, Hiroshi; Dohi, Kaoru; Machida, Hirofumi; Takeuchi, Hideyuki; Aoki, Toshikazu; Nishimura, Hiroyuki; Yasutomi, Masashi; Senga, Michiharu; Ichikawa, Takehiko; Kakuta, Kentaro; Mizutani, Yasuhide; Tanoue, Akiko; et al. (Circulation Journal, 2018)
Background:The aim of this study was to assess the echocardiographic characteristics of chronic hemodialysis (HD) patients with end-stage renal disease (ESRD) in a multicenter prospective cohort study.Methods and Results:Three hundred and fifteen patients with ESRD (67.9±10.6 years, 47.6% male) on chronic HD for ≥1 year were examined on transthoracic echocardiography, including Doppler-derived aortic valve area (AVA) measurement. Only 11.5% and 3.4% of all patients had normal left ventricular (LV) geometry and normal LV filling pattern, respectively. The majority of patients had aortic and mitral valvular calcification, and approximately 50% of all 315 patients had aortic valve narrowing with AVA <2.0 cm2. Patients were divided into 3 groups according to AVA index tertile: group 1, highest tertile; group 2, middle tertile; and group 3, lowest tertile. Group 3 was older, had a greater cardiothoracic ratio on chest X-ray, higher plasma brain natriuretic peptide and total LV afterload, and lower stroke volume index than the other 2 groups. Age and intact parathyroid hormone (PTH) level were independently associated with low AVA index.Conclusions:Patients with ESRD on chronic HD have a high prevalence of cardiac structural and functional abnormalities including calcified aortic sclerosis. High age and PTH were associated with aortic valve narrowing in these patients.